Kharkiv period of activity professor P.F. Tushkan (1934-1942) - V. O. Volovodovska (History of science and technology, 2018)
The way of life and creative victories of P.F. Tushkan, his achievements in the field of formation and development of agrarian science in Ukraine are analyzed. Among them, the Kharkiv period occupies a special place during which the scientist worked as a senior researcher of the All-Ukrainian Academy of Agricultural Sciences (1934-1936), and in 1936 he was freelance to the Ukrainian Research Institute of Socialist Agriculture, where he worked on the scientific task «Drought and their impact on the crops of the Ukrainian SSR». He argued that taking measures to deal with drought is not necessary when it came, but in advance. According to research results P.F. Tushkan forms a publication, which, based on the recommendations of the Institute and the РCCLA of the Ukrainian SSR, was decided to publish after receiving expert reviews. After their getting, the book was revised, but the Institute was not able to print it. The treatment of Pavlo Fedorovych to the president of VASKHNIL, and later on May 24, 1940, to the Presidium of VUAN, in order to facilitate a review of the book and its publication, were not successful. Almost a year later, on August 20, 1941, the scientist appealed to the leadership of the Ukrainian Research Institute for Socialist Agriculture, with a request to publish his article «Agricultural drought and their study» and at the same time wrote a letter to the academician of the Academy of Sciences of the USSR and VASGNIL O.N. Sokolovskyi concerning the promotion of his long-term research work on the study of drought in the press. After studying the publication, Sokolovskyi gave a conclusion to P.F. Tushkan in which he noticed the importance and usefulness of publishing a book for specialists. In October 1941, the scientist appealed to the Ukrainian Research Institute of Socialist Agriculture with a desire to transfer the materials of his work on the study of droughts in the Ukrainian SSR, but as a result of the invasion of the German troops to Kharkov, the Institute did not have time to evacuate and their fate remained unknown. The health of Pavlo Fedorovich has deteriorated significantly owing to the exhaustion of malnutrition, which in turn provoked paralysis of the heart and in the winter of 1942 the scientist died. Now, once the pioneering discovery of the world dimension is made by P.F. Tushkan, in connection with the fact that droughts in the steppes of Ukraine are of a periodic nature and associated with solar activity, has become axiomatic, but its authorship belongs to others.